Export Competitiveness Of Indonesia's Crude Palm Oil (CPO) In The Indian Market - Nasution, Suhela Putri; Hasibuan, Abdurrozzaq (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
One of Indonesia's primary export commodities is CPO. CPO is a significant source of foreign cash for the nation because it can produce 80% of the total value of Indonesian agricultural exports. The Indian market, the world's largest purchaser of CPO, is Indonesia's primary export destination. This study aims to determine how competitive Indonesian CPO is in the Indian market with rivals Malaysia and Thailand. The secondary data used is a time series from 2018 to 2022 gathered from several domestic and foreign organizations. This research method uses the Revealed Comparative Advantage (RCA) analysis to determine Indonesia's competitiveness.